Ultraviolet Background Radiation from Not-So-Dark Matter in the Galactic Halo - Richard Conn Henry; Jayant Murthy; James Overduin (Universe)
Murthy et al. (2025) (hereafter Paper I) have recently reported the discovery of unexpectedly bright diffuse extreme-ultraviolet radiation at high latitudes in both the Northern and Southern Galactic Hemispheres. After correction for extinction by the total interstellar dust in the direction of each observation, the spectra are nearly identical, suggesting that the radiation has a unique source and likely originates in the halo of our galaxy. The observed spectrum extends down to 912 Å, the interstellar hydrogen absorption edge. Radiation even slightly short of that edge would, if ubiquitous, be sufficient to explain the high degree of ionization in our galaxy and throughout the universe. We hypothesize that this newly discovered radiation originates in the slow decay of dark matter. The intensity of the radiation implies that the decay cannot be via the weak interaction, suggesting the existence of a new, even weaker fundamental interaction, consistent with the exceedingly long decay lifetime required.